2019
DOI: 10.4103/1673-5374.253524
|View full text |Cite
|
Sign up to set email alerts
|

Time-course pattern of neuronal loss and gliosis in gerbil hippocampi following mild, severe, or lethal transient global cerebral ischemia

Abstract: Transient ischemia in the whole brain leads to neuronal loss/death in vulnerable brain regions. The striatum, neocortex and hippocampus selectively loose specific neurons after transient ischemia. Just 5 minutes of transient ischemia can cause pyramidal neuronal death in the hippocampal cornu ammonis (CA) 1 field at 4 days after transient ischemia. In this study, we investigated the effects of 5-minute (mild), 15-minute (severe), and 20-minute (lethal) transient ischemia by bilateral common carotid artery occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…Interestingly, it has been reported that scutellarin and/or chlorogenic acid display neuroprotective effects against brain ischemic insults in rodents ( 27 , 28 ). Therefore, the objective of this research was to analyze scutellarin and chlorogenic acid in YES-10 ® and examine the antioxidant efficacy of YES-10 ® in neuroprotection against ischemic injury induced by 5-min transient forebrain ischemia in gerbils, which have been used as a model of transient ischemia (TI) in the forebrain ( 19 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been reported that scutellarin and/or chlorogenic acid display neuroprotective effects against brain ischemic insults in rodents ( 27 , 28 ). Therefore, the objective of this research was to analyze scutellarin and chlorogenic acid in YES-10 ® and examine the antioxidant efficacy of YES-10 ® in neuroprotection against ischemic injury induced by 5-min transient forebrain ischemia in gerbils, which have been used as a model of transient ischemia (TI) in the forebrain ( 19 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have reported that ischemia-mediated neuronal loss/death in the caudate–putamen is different in the pattern of neuronal death according to the subregions of the caudate–putamen and ischemic duration (15 and 30 min) in a rat model of transient focal brain ischemia induced by middle cerebral artery occlusion (MCAO) [ 3 ]. In addition, it has been reported that a severer aspect of neuronal loss/death in the hippocampus is shown following 15 min of TFI than that in 5 min TFI in gerbils [ 2 ]. Furthermore, a rat model of focal brain ischemia induced by MCAO for over 1 h develops infarct lesion (necrotic tissue) which is easily visualized by 2, 3, 5-triphenyltetrazolium chloride (TTC) assay, but infarction does not occur in the brain induced by TFI for 5–15 min in gerbils when the TTC assay is applied, in which selective neuronal death only occurs [ 1 , 15 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described [ 2 , 10 , 35 ], corresponding immunoreactive structures were analyzed in the CA1 region. Seven sections/gerbil were selected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations